Antioxidant Properties of Alien Plant Species: Assessing Phenolic and Flavonoid Content, Antioxidant, Oxidant Capacities, and Antimicrobial Activity - Burović, Selma; Pašić, Lejla; Madacki-Todorović, Kamelija; Sarajlić, Nermina; Galijašević, Semira (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2025)
Alien plant species pose significant threats to natural ecosystems due to their adaptability and invasive potential. In this study, the antioxidant activity of 13 alien and invasive plant species was investigated, regarding their total phenolic content, flavonoid content, total antioxidant capacity, total oxidant capacity, and antimicrobial activity. Plant tissues were macerated, evaporated to dryness, and the extracts were dissolved in water. Total phenolic content ranged from 6.55 mg GAE/g extract to 30.82 mg GAE/g extract. Flavonoid content spanned from 3.04 mg Quercetin/g extract to 40.81 mg Quercetin/g extract. The total antioxidant capacity ranged between 662 CEAC µM and 1540 CEAC µM. Total oxidative capacity can be correlated to the abiotic stress. Rhus typhina L. and Impatiens balfourii Hooker f., exhibited positive total oxidant capacity values of 122.56 ± 7.85 µM H₂O₂ Equiv./L and 141.38 ± 4.33 µM H₂O₂ Equiv./L, respectively. These two species also showed the highest total antioxidant capacity that were 1190,06 ± 137,36 CEAC µM for Rhus typhina L and 1540,34 ± 270,84 for CEAC Impatiens balfourii Hooker f. The results suggest that the extraction solvent significantly affects the antioxidant capacity, with ethanol generally providing higher extraction efficiency for many species. The antimicrobial activity was determined against Escherichia coli, Staphylococcus aureus, Proteus mirabilis, Pseudomonas aeruginosa, and Candida albicans. Rhus typhina L was active against E. coli and P. mirabilis. This data indicates that plants increased antioxidant defense systems against abiotic stresses. Clearly, the correlation between total oxidant capacity and total antioxidant capacity values in plants is a valuable factor indicating the mechanism of the plant defense.